A comment on Wong and Waite, "Elder mistreatment predicts later physical and psychological health: Results from a national longitudinal study, " JEAN Issue 29(1), pp. 15–42. Issue 2 (27th May 2017) - Acierno, Ron
ABSTRACT: Wong and Waite present a longitudinal study of elder abuse and its effects. However, they contend that their data do not support the protective effects of social support, a finding in contrast with virtually all existing research on the topic. Closer inspection of their variables indicates that they misclassify elder abuse insofar as their results are actually in terms of only one type of elder abuse, psychological abuse, ignoring physical and sexual abuse. They also define "elder abuse" using only one question: "Is there anyone who insults you or puts you down?" Finally, they measure social support with the single item: "if they generally feel they can open up to, and rely on, these significant others." It is not, therefore, surprising that they observed that social support was not protective considering health outcomes.